Ethical Aspects of AI in Language Learning Management: A Literature Review - Sabudu, Delli (International Journal Labs, 2025)
The rapid integration of Artificial Intelligence (AI) into language learning management systems has transformed pedagogical practices through its personalization, efficiency, and adaptive feedback. Nevertheless, this transformation raises significant ethical concerns that demand critical scholarly attention. This study presents a systematic literature review examining the ethical dimensions of AI implementation in language learning management, titled Ethical Aspects of AI in Language Learning Management: A Literature Review. The review focuses particularly on data privacy and security, algorithmic bias, transparency, accountability, learner autonomy, and the evolving roles of educators and learners. It synthesizes findings from major academic databases, including Scopus, Web of Science, and ERIC, in accordance with PRISMA guidelines, drawing on peer-reviewed studies published between 2013 and 2023. The findings indicate that while AI demonstrates considerable pedagogical potential, its unregulated implementation may intensify educational disparities, compromise academic integrity, diminish human interaction, and erode critical thinking skills. Scholars increasingly agree on the urgent need for comprehensive ethical frameworks, AI literacy development, and multi-stakeholder governance to ensure responsible and equitable AI integration in language education. This review makes a significant contribution to the field by mapping dominant ethical challenges, identifying research gaps, and proposing directions for future empirical studies and policy development. Ultimately, the study posits that ethical foresight and human-centered design must remain central to AI-enhanced language learning to preserve the humanistic foundations of language education.